DISPUTES IN THE APPLICATION OF EMPLOYMENT COPYRIGHT LAW RELATING TO THE PRINCIPLE OF STRICT LIABILITY IN ENVIRONMENTAL CLUSTERS - Mashudi, Mashudi; Basid, Abdul (IBLAM LAW REVIEW, 2024)
Numerous conflicts have arisen since the Omnibus Law-based Job Creation Law was passed, particularly in the environmental cluster. In this instance, it is evident in the environmental cluster of Article 22 Number 33 of the Job Creation Law, where the phrase "without the need to prove elements of error" is omitted, leading to ambiguity in its meaning. Subsequently, the legal ramifications for law enforcement, settlement quality, and environmental preservation; following this, the legal ramifications for land fire and forest fire incidents; and last, the indirect legal ramifications for environmental legal politics. As the owner of the authority, the government should review and revise the Job Creation Law in the environmental cluster and strengthen the law enforcement system in order to achieve justice and a sustainable development without ignoring the protection and management of the environment so that its sustainability is always maintained both now and in the future. This is because the government is best suited to manage matters like these, which have connections to law enforcement and other important legal components. It's likely that the data from this study will be useful for future research on the environment or other subjects..